Comparison of different doses of chlorocholine chloride applied on herbaceous cotton - Pípolo, Antonio Eduardo; Athayde, Manoel Luiz Ferreira; Pípolo, Valeria Carpentieri; Parducci, Salvador (Pesquisa Agropecuaria Brasileira, 1993)
The experiment was done at the Experimental Farm of the Faculdade de Ciências Agrárias e Veterinárias of the UNESP, "Campus" at Jaboticabal, SP, Brazil, during the 1988/1989 growing season. The aim of this work was to evaluate the growth regulator CCC on the cotton plant (Gossypium hirsutum L.) cv. 'IAC-19'. The cotton plants, cultivar 'IAC-19', were sprayed 70 days after emergence at the rates of 0, 25, 50 and 100 g/ha of CCC. Another treatment was done with two sprayings, 15 days apart, at the rate of 25 g/ha each. The CCC caused a 20% average reduction in plant height, limiting it to less than 1.5 m and thus easing the harvest operation. There were no significant differences in yields but the 25 g/ha dose resulted in yield increases of 11.5% and 11.6% when applied once or twice, respectively. These treatments increased earliness of yield. The CCC increased seed weight and micronaire.